2006
DOI: 10.1007/s10404-006-0111-x
|View full text |Cite
|
Sign up to set email alerts
|

Glass reflow on 3-dimensional micro-apertures for electrophysiological measurements on-chip

Abstract: We propose a new method to fabricate micro-apertures for on-chip electrophysiological measurements of living cells. Thermal reflow of phosphosilicate glass (PSG) is applied to funnel-or nozzle-type microstructures to generate very smooth surfaces on the finalized chip. Such 3-dimensional microstructures show close similarities to fire-polished glass pipette tips. Immobilized cells fit perfectly to these structures offering a large contact area for sealing between the cell membrane and the oxide surface. A tigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Plasma treatment of the polyimide surface followed by poly-L-lysine functionalization rendered the surface hydrophilic, thus favoring giga-seal formation. Also, the polymide surface around the aperture is smooth: a 1 nm root-mean-square surface roughness was recorded by atomic force microscopy (AFM, not shown), in-line with published roughness data for efficient cell-to-surface seals (Lehnert et al 2007). From the SEM cross-section shown in Fig.…”
Section: Electrophysiological Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Plasma treatment of the polyimide surface followed by poly-L-lysine functionalization rendered the surface hydrophilic, thus favoring giga-seal formation. Also, the polymide surface around the aperture is smooth: a 1 nm root-mean-square surface roughness was recorded by atomic force microscopy (AFM, not shown), in-line with published roughness data for efficient cell-to-surface seals (Lehnert et al 2007). From the SEM cross-section shown in Fig.…”
Section: Electrophysiological Results and Discussionsupporting
confidence: 84%
“…Gigaseal formation is poorly understood, but published studies on planar patch-clamp systems have suggested the importance of several parameters. The surface making contact with the cell membrane should be smooth, clean and hydrophilic; it should have a high area of contact with the cell membrane, thus favoring an hourglass shape for the aperture (Chen et al 2009, Lehnert et al 2007, Sordel et al 2006. The type of cells, their passage number and minimal debris in the cell suspension also play a role.…”
Section: Electrophysiological Results and Discussionmentioning
confidence: 99%
“…In the last decade, planar patch-clamp chips have been proven useful to replace traditional micropipette for ion channel recording (Dunlop et al, 2008). Various substrate materials and chip configurations were demonstrated to measure different types of cells and ion channel functions (Fertig et al, 2002;Lau et al, 2006;Lehnert et al, 2007;Li et al, 2006;Milligan et al, 2009;Py et al, 2010). Microscope, micromanipulator, and skilled operator is essentially not required; hence, automated and parallel-executed ion channel recording were further developed to enhance the throughput for drug discovery and side effect screening (e.g., human ether-a-go-go-related gene) (Bruggemann et al, 2006;Finkel et al, 2006;Mathes, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Advances in microfluidic technologies have led to the development of microdevices for single-cell electrical property characterization. The three types of microdevices for electrical characterization are based on patch clamp, [21][22][23][24][25][26][27][28][29][30][31][32][33][34] electrorotation, [35][36][37][38][39][40] and micro-electrical impedance spectroscopy ͑-EIS͒.…”
Section: Introductionmentioning
confidence: 99%